130 years to the oldest department of hygiene in Russia - P. I. Melnichenko; N. I. Prokhorov; V. I. Arkhangelsky (Сеченовский вестник)
The article presents a brief outline of the history of the chair of general hygiene of the First Moscow State Medical University named after I.M. Sechenov. The characteristic of activities of the department as a whole and its individual members at the general historical background of the XIX–XX centuries is given in this paper.